FACTORS INFLUENCING SALES DECISIONS AND THEIR IMPACT ON MICRO, SMALL AND MEDIUM ENTERPRISES IN BRAVO PHOTOCOPY BUSINESS BLANG PULO VILLAGE - Wahyuni , Yuyun; Khairani Husna , Fadhila; Haway , Fitra; Aulia Ramadhan, Hafidz; Sinta, Irada (RADJA PUBLIKA, 2023)
This study aims to find out the sales decisions and their impact on micro, small and medium enterprises in the blang pulo village photocopy business. The research method used is the survey method. The survey research method uses data collection and analysis techniques in the form of opinions / facts from the subject under study (respondents) through question and answer which is directly communicated with the respondents, and interviews (oral questions) conducted with face-to-face communication. This research is qualitative which means descriptive research and tends to use analysis with an inductive approach.